Citrate‐based biphasic scaffolds for the repair of large segmental bone defects. Issue 2 (29th May 2014) - Guo, Ying; Tran, Richard T.; Xie, Denghui; Wang, Yuchen; Nguyen, Dianna Y.; Gerhard, Ethan; Guo, Jinshan; Tang, Jiajun; Zhang, Zhongming; Bai, Xiaochun; Yang, Jian
Abstract: Attempts to replicate native tissue architecture have led to the design of biomimetic scaffolds focused on improving functionality. In this study, biomimetic citrate‐based poly (octanediol citrate)‐click‐hydroxyapatite (POC‐Click‐HA) scaffolds were developed to simultaneously replicate the compositional and architectural properties of native bone tissue while providing immediate structural support for large segmental defects following implantation. Biphasic scaffolds were fabricated with 70% internal phase porosity and various external phase porosities (between 5 and 50%) to mimic the bimodal distribution of cancellous and cortical bone, respectively. Biphasic POC‐Click‐HA scaffolds displayed compressive strengths up to 37.45 ± 3.83 MPa, which could be controlled through the external phase porosity. The biphasic scaffolds were also evaluated in vivo for the repair of 10‐mm long segmental radial defects in rabbits and compared to scaffolds of uniform porosity as well as autologous bone grafts after 5, 10, and 15 weeks of implantation. The results showed that all POC‐Click‐HA scaffolds exhibited good biocompatibility and extensive osteointegration with host bone tissue. Biphasic scaffolds significantly enhanced new bone formation with higher bone densities in the initial stages after implantation. Biomechanical and histomorphometric analysis supported a similar outcome with biphasic scaffolds providing increased compression strength, interfacial bone ingrowth, and periosteal remodeling in early time points, but were comparable to all experimental groups after 15 weeks. These results confirm the ability of biphasic scaffold architectures to restore bone tissue and physiological functions in the early stages of recovery, and the potential of citrate‐based biomaterials in orthopedic applications. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 772–781, 2015.